2010
DOI: 10.1115/1.3104614
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of the Internal Cooling Channels of a High Pressure Turbine Blade—Part I: Methodology

Abstract: This first paper describes the conjugate heat transfer (CHT) method and its application to the performance and lifetime prediction of a high pressure turbine blade operating at a very high inlet temperature. It is the analysis tool for the aerothermal optimization described in a second paper. The CHT method uses three separate solvers: a Navier–Stokes solver to predict the nonadiabatic external flow and heat flux, a finite element analysis (FEA) to compute the heat conduction and stress within the solid, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Output:ω k ,x k , 1 ≤ k ≤ d 1 Initialization: Z = ∅, k = 0,ω = 0 and r 0 = g while r k 2 > g 2 do A reduced quadrature is also used to accelerate the integral computation in (6). The remaining integral computations in (5) are Ω f µ · ψ i and ∂Ω N T N,µ · ψ i . They do not depend on the current solution, but only on the loading of the online variability µ, which is no longer efficient for nonparametrized variabilities.…”
Section: Reduced Order Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Output:ω k ,x k , 1 ≤ k ≤ d 1 Initialization: Z = ∅, k = 0,ω = 0 and r 0 = g while r k 2 > g 2 do A reduced quadrature is also used to accelerate the integral computation in (6). The remaining integral computations in (5) are Ω f µ · ψ i and ∂Ω N T N,µ · ψ i . They do not depend on the current solution, but only on the loading of the online variability µ, which is no longer efficient for nonparametrized variabilities.…”
Section: Reduced Order Modelingmentioning
confidence: 99%
“…These blades are responsible for a large part of the maintenance budget of the engine, with temperature creep rupture and high-cycle fatigue [35,18] as possible failure causes. Various technological efforts have been spent to increase the durability of these blades as much as possible, such as thermal barrier coatings [43], advanced superalloys [10] and complex internal cooling channels [5,46], see Figure 1 for a representation of a high-pressure turbine blade. Figure 1: Illustration of a high-pressure turbine blade [1].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has already been invested in studying the performance optimization in pump [4][5][6][7] and turbomachines [8][9][10]. There are various methods to optimize the design geometry, including global optimization algorithms based on heuristic algorithms and gradient-based methods.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the FCE on the suction side was usually higher than that on the pressure side except the secondary vortices regions, and the upstream wakes could reduce the blade surface's FCE. Amaral et al [6] carried out the aerothermal analysis and optimization of a GTB based on the lifetime model, and the result showed that the blade lifetime could be extended by using the optimization procedure without increasing the amount of the cooling flow and the complexity of the cooling channel. Xu et al [7] employed a duplex-medium cooling method combining air and steam as coolants to investigate the cooling performance of a turbine vane, and the experimental result showed that the performance increased with the increases in the steam flow rate and coolant pressure, as well as the decrease in the coolant temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the cooling problems of the gas-turbine blade (GTB) should be specially paid attention, and many scholars have shown great interests in these problems [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%